The Study of Antiviral Drugs' Activity Against The Causative Agent of Zika Fever in Cell Culture - S. Ya. Loginova; V. N. Shchukina; G. V. Borisevich; I. V. Surovyatkina; S. V. Borisevich (Антибиотики и Химиотерапия)
Zika virus (ZIKV) is a representative of the viruses of the genus Flavivirus in the family Flaviviridae, it belongs to the zoonotic arbovirus infections transmitted by mosquitoes of the genus Aedes. In humans, this flavivirus causes a disease known as zika fever, etymologically related to yellow fever, dengue, West Nile and Chikungunya viruses. There is no specific treatment for zika fever, just as there is no vaccine or preventive measures available to date. A comparative analysis of the effectiveness of chemotherapy medications, interferon inducers and two classes of interferon α-, β-, and γ- showed that interferon drugs effectively inhibit the reproduction of Zika virus in Vero cell culture in a wide range of concentrations. Chemotherapy medications Triazavirin®, Virazole®, Zovirax®, Cytarabine®, and Ingavirin® did not affect the reproduction of Zika virus strain MR 766V in Vero cell culture. The size of negative Zika virus colonies was significantly reduced in the presence of Virazole® and Ribavirin® at a concentration of 100 μg/ml. zika virus, Triazavirin®, Ribavirin®, Ingavirin®, Reaferon-EU®, Rebif(fila)®, antiviral efficacy